Workshop Pentingnya Peningkatan Indeks Pembangunan Manusia Dalam Menghadapi Berbagai Isu Kependudukan - Hestiana, Agustri; Illahi , Maman; Sutana, Muhammad Habib Luthfi; Habibullah, Zain; Sari , Putri Lupita (Universitas Dehasen Bengkulu, 2023)
This workshop discussed the important role of improving the Human Development Index (HDI) in addressing various population-related issues. HDI is key in measuring a country's progress in terms of social welfare, health, and education. In the context of globalization and economic development, improving HDI has become a top priority for many countries. It is important to ensure that every individual has fair and equal access to educational opportunities and health services. This workshop will outline the challenges faced in improving HDI, including limited access to quality education, economic disparities, and gender inequality. One of the main focuses of the workshop is how to encourage active community participation in efforts to improve HDI. Collaboration between the government, private sector, and non-governmental organizations is considered essential in achieving this goal. Population issues such as rapid population growth, uncontrolled urbanization, and demographic change were highlighted in this workshop. It is important to develop holistic and sustainable strategies to address these issues. Education is recognized as a major factor in improving HDI. This workshop will highlight innovative efforts in improving access and quality of education, especially in remote and marginalized areas. Not only education, but also access to services Quality health is a key element in efforts to improve HDI. This workshop will discuss strategies to improve accessibility and sustainability of basic health services. Women's empowerment is considered an important step in improving a country's HDI. This workshop will highlight the role of women in social and economic development and efforts to reduce gender disparities. In the context of sustainable development, this workshop will discuss the importance of integrating social, economic and environmental aspects in efforts to improve HDI. This includes aspects such as environmental sustainability and adaptation to climate change. Through discussions and exchange of experiences, the workshop aims to generate concrete recommendations and practical solutions to effectively improve HDI and address population issues. It is hoped that the outcomes of this workshop can guide public policies and development practices in various countries.